University Image: A strategic moderator between Justice Dimensions and Service Recovery Satisfaction in Open and Distance Learning (ODL) context? - Mohd Rushidi Mohd Amin Dr; Vinesh Maran Sivakumaran Dr (Adult Education Research Conference, 2023)
This study investigated the relationships between perceived justice with justice dimensions (distributive, procedural, interpersonal, and informational), university image, service recovery satisfaction through a survey of 303 ODL students in Malaysia who experienced a service failure and subsequently a service recovery effort.
Keywords: Justice Dimensions; Service Recovery Satisfaction; University Image; Open and Distance Learning (ODL); and PLS – SEM.